Elevated C-reactive protein and posttraumatic stress pathology among survivors of the 9/11 World Trade Center attacks. (June 2017) - Rosen, Rebecca L.; Levy-Carrick, Nomi; Reibman, Joan; Xu, Ning; Shao, Yongzhao; Liu, Mengling; Ferri, Lucia; Kazeros, Angeliki; Caplan-Shaw, Caralee E.; Pradhan, Deepak R.; Marmor, Michael; Galatzer-Levy, Isaac R.
Abstract: Background: Systemic inflammation has emerged as a promising marker and potential mechanism underlying post-traumatic stress disorder (PTSD). The relationship between posttraumatic stress pathology and systemic inflammation has not, however, been consistently replicated and is potentially confounded by comorbid illness or injury, common complications of trauma exposure. Methods: We analyzed a large naturalistic cohort sharing a discrete physical and mental health trauma from the destruction of the World Trade Center (WTC) towers on September 11, 2001 (n = 641). We evaluated the relationship between multiple physical and mental health related indices collected through routine evaluations at the WTC Environmental Health Center (WTC EHC), a treatment program for community members exposed to the disaster. C-Reactive Protein (CRP), a marker of systemic inflammation, was examined in relation to scores for PTSD, PTSD symptom clusters (re-experiencing, avoidance, negative cognitions/mood, arousal), depression and anxiety, while controlling for WTC exposures, lower respiratory symptoms, age, sex, BMI and smoking as potential risks or confounders. Results: CRP was positively associated with PTSD severity ( p < 0 .001), trending toward association with depression ( p = 0.06), but not with anxiety ( p = 0.27). CRP was positively associated with re-experiencing ( p < 0 .001) and avoidance ( p < 0 .05) symptom clusters, and trended toward associations with negative cognitions/mood ( p = 0.06) and arousal ( p = 0.08). Conclusions: In this large study of the relationship between CRP and posttraumatic stress pathology, we demonstrated an association between systemic inflammation and stress pathology (PTSD; trending with depression), which remained after adjusting for potentially confounding variables. These results contribute to research findings suggesting a salient relationship between inflammation and posttraumatic stress pathology.